Mitogen-Activated Protein Kinase Expression Profiling Revealed Its Role in Regulating Stress Responses in Potato (Solanum tuberosum) - Madiha Zaynab; Athar Hussain; Yasir Sharif; Mahpara Fatima; Mateen Sajid; Nazia Rehman; Xuewei Yang; Khalid Ali Khan; Hamed A. Ghramh; Shuangfei Li (Plants, 2021)
Mitogen-activated protein kinase (MAPK) cascades are the universal signal transduction networks that regulate cell growth and development, hormone signaling, and other environmental stresses. However, their essential contribution to plant tolerance is very little known in the potato (Solanum tuberosum) plant. The current study carried out a genome-wide study of StMAPK and provided a deep insight using bioinformatics tools. In addition, the relative expression of StMAPKs was also assessed in different plant tissues. The similarity search results identified a total of 22 StMAPK genes in the potato genome. The sequence alignment also showed conserved motif TEY/TDY in most StMAPKs with conserved docking LHDXXEP sites. The phylogenetic analysis divided all 22 StMAPK genes into five groups, i.e., A, B, C, D, and E, showing some common structural motifs. In addition, most of the StMAPKs were found in a cluster form at the terminal of chromosomes. The promoter analysis predicted several stress-responsive Cis-acting regulatory elements in StMAPK genes. Gene duplication under selection pressure also indicated several purifying and positive selections in StMAPK genes. In potato, StMAPK2, StMAPK6, and StMAPK19 showed a high expression in response to heat stress. Under ABA and IAA treatment, the expression of the total 20 StMAPK genes revealed that ABA and IAA played an essential role in this defense process. The expression profiling and real-time qPCR (RT-qPCR) exhibited their high expression in roots and stems compared to leaves. These results deliver primary data for functional analysis and provide reference data for other important crops.